Let x 1 < x 2 < x 3 be three distinct roots of the equation : ⌊ x ⌋ − 1 = { x } and y 1 < y 2 < y 3 be three distinct roots of the equation : ⌈ y ⌉ − 1 = { y } . [ Here ⌈ p ⌉ denotes least integer greater than or equal to p , ⌊ p ⌋ denotes greatest integer less than or equal to p and { p } denotes fractional part of p ] . Then if :
⌊ x 2 − y 2 ⌋ − { x 1 − y 1 } + ⌈ x 3 − y 3 ⌉ = a
and x 1 2 x b 1 − y 1 y b 2 2 = 2 y b 3 − x b 4 where b 1 , b 2 , b 3 and b 4 are subscripts of x and y and 1 ≤ b i ≤ 3 , i = { 1 , 2 , 3 , 4 } , b i ∈ N with all the b i not being equal. Find ⌊ a + b 1 + b 2 + b 3 + b 4 ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We know that 0 ≤ { x } < 1
⇒ 0 ≤ ⌊ x ⌋ − 1 < 1
⇒ 1 ≤ ⌊ x ⌋ < 2 ⇒ 1 ≤ ⌊ x ⌋ < 4 ⇒ ⌊ x ⌋ ∈ { 1 , 2 , 3 } . Now putting the values of ⌊ x ⌋ in the equation ⌊ x ⌋ − 1 = { x } we will get the corresponding values of { x } as { x } = { 0 , 2 − 1 , 3 − 1 } .
Now we know x = ⌊ x ⌋ + { x } .By putting the corresponding values of ⌊ x ⌋ and { x } we get
x 1 = 1 x 2 = 1 + 2 x 3 = 2 + 3
Similarly solving for y ,
0 ≤ ⌈ y ⌉ − 1 < 1
⇒ 1 ≤ ⌈ y ⌉ < 2 ⇒ 1 ≤ ⌈ y ⌉ < 4 ⇒ ⌈ y ⌉ ∈ { 1 , 2 , 3 } . Now putting the values of ⌈ y ⌉ in the equation ⌈ y ⌉ − 1 = { y } we will get the corresponding values of { y } as { y } = { 0 , 2 − 1 , 3 − 1 } .
We know ⌊ y ⌋ = ⌈ y ⌉ − 1 , when y ∈ / Z and ⌊ y ⌋ = ⌈ y ⌉ = y , when y ∈ Z
Using these equations, we get the corresponding values of ⌊ y ⌋ as ⌊ y ⌋ = { 1 , 1 , 2 }
Again using y = ⌊ y ⌋ + { y } .By putting the corresponding values of ⌊ y ⌋ and { y } we get
y 1 = 1 y 2 = 2 y 3 = 1 + 3
Now, ⌊ x 2 − y 2 ⌋ − { x 1 − y 1 } + ⌈ x 3 − y 3 ⌉ = ⌊ ( 1 + 2 ) − 2 ⌋ − { 1 − 1 } + ⌈ ( 2 + 3 ) − ( 1 + 3 ) ⌉ = 1 − 0 + 1 = 2 .
⇒ a = 2
Finding all the possible values of 2 y b 3 − x b 4 we get
2 y 1 − x 1 = 2 ( 1 ) − 1 = 1 2 y 1 − x 2 = 2 ( 1 ) − ( 1 + 2 ) = 1 − 2 2 y 1 − x 3 = 2 ( 1 ) − ( 2 + 3 ) = − 3
2 y 2 − x 1 = 2 2 − 1 2 y 2 − x 2 = 2 2 − ( 1 + 2 ) = 2 − 1 2 y 2 − x 3 = 2 2 − 2 − 3
2 y 3 − x 1 = 2 ( 1 + 3 ) − 1 = 1 + 2 3 2 y 3 − x 2 = 2 ( 1 + 3 ) − ( 1 + 2 ) = 1 + 2 3 − 2 2 y 3 − x 3 = 2 ( 1 + 3 ) − ( 2 + 3 ) = 3
Now finding all the possible values of x 1 2 x b 1 − y 1 y b 2 2 we get
∵ x 1 = y 1 = 1 our expression becomes x b 1 − y b 2 2
x 1 − y 1 2 = 1 − 1 2 = 0 x 1 − y 2 2 = 1 − ( 2 ) 2 = − 1 x 1 − y 3 2 = 1 − ( 1 + 3 ) 2 = − 3 − 2 3
x 2 − y 1 2 = ( 1 + 2 ) − 1 2 = − 2 x 2 − y 2 2 = ( 1 + 2 ) − ( 2 ) 2 = 2 − 1 x 2 − y 3 2 = ( 1 + 2 ) − ( 1 + 3 ) 2 = 2 − 3 − 2 3
x 3 − y 1 2 = ( 2 + 3 ) − 1 = 1 + 3 x 3 − y 2 2 = ( 2 + 3 ) − ( 2 ) 2 = 3 x 3 − y 3 2 = ( 2 + 3 ) − ( 1 + 3 ) 2 = − 2 − 3
Matching all the expressions we get 2 possible values of { b 1 , b 2 , b 3 , b 4 }
{ b 1 , b 2 , b 3 , b 4 } 1 = { 2 , 2 , 2 , 2 } and { b 1 , b 2 , b 3 , b 4 } 2 = { 3 , 2 , 3 , 3 } but according to question all the b i are not equal. So first case is not considered.
So, b 1 = 3 , b 2 = 2 , b 3 = 3 , b 4 = 3
Hence our answer is 2 + 3 + 2 + 3 + 3 = 1 3